How and when intragroup relationship conflict leads to knowledge hiding: the roles of envy and trait competitiveness - Peng, He; Bell, Chris; Li, Yiran (The International journal of conflict management, 2021)
Purpose Although studies have demonstrated that knowledge hiding is an important inhibitor of organizational innovation, current research does not clearly address how intragroup relationship conflict influences knowledge hiding. This study aims to identify the underlying mechanism between intra-group relationship conflict and knowledge hiding. Design/methodology/approach Drawing on affective events theory (AET), the authors propose a theoretical model and empirically test it by applying hierarchical regression analysis and a bootstrapping approach to data from a multi-wave survey of 224 employees in China. Findings Consistent with AET, the empirical results show that envy mediates perceived intragroup relationship conflict and knowledge hiding. As predicted, trait competitiveness moderates the indirect effect of perceived intragroup relationship conflict on knowledge hiding via envy. Originality/value The results support an AET perspective whereby knowledge hiding is shaped by relationship conflict, envy and trait competitiveness. This study introduces the novel proposition that relationship conflict and competitiveness influence envy, and consequently knowledge hiding.